2016
DOI: 10.1002/lt.24400
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of microRNA‐18a and microRNA‐199a‐5p to hepatocellular carcinoma recurrence after living donor liver transplantation

Abstract: There are few reports about recurrence-related microRNAs (miRNAs) after liver transplantation (LT) for hepatocellular carcinoma (HCC). The purpose of this study was to identify novel recurrence-related miRNAs after living donor liver transplantation (LDLT) for HCC. First, we performed microarray analyses of samples from a liver with primary HCC, a liver that was noncancerous, and a liver that had recurrence-metastasis from 3 patients with posttransplant recurrence. Then we selected miRNAs with consistently alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 52 publications
0
23
1
1
Order By: Relevance
“…Six researches [ 1 , 4 , 11 14 ] concentrated on the relationship between high blood miR-122 level and OS, manifesting that there was no significant correlation between high blood miR-122 level and OS (HR = 0.89, 95% CI = 0.49–1.60, P = 0.69, Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Six researches [ 1 , 4 , 11 14 ] concentrated on the relationship between high blood miR-122 level and OS, manifesting that there was no significant correlation between high blood miR-122 level and OS (HR = 0.89, 95% CI = 0.49–1.60, P = 0.69, Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…In clinical studies, miR-18a expression strongly correlated with clinical TNM stage, tumor differentiation and regional lymph node metastasis (P < 0.005), and miR-18a upregulation is negatively associated with the clinical response of NSCLC because it decreases the sensitivity of cells to radiation by activating the serine/threonine-protein kinase 4 (STK4) pathway [15]. Furthermore, high miR-18a expression was correlated with a high recurrence rate in hepatocellular X. Xu et al miR-18a, miR-20a, and miR-92a in NSCLC carcinoma (HCC) by promoting pathological angiogenesis via an increase in VEGFA expression [35]. In accordance with previous findings, our study found that high plasma miR-18a expression correlated with shorter survival, and was an independent risk factor for DFS and OS in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-18a, as an oncogene, promotes the tumorigenesis and tumor angiogenesis 46 , 47 . Besides, miR-18a promotes pathological angiogenesis by increasing VEGFA expression in hepatocellular carcinoma (HCC) 48 . In addition, some evidences have demonstrated that miR-18a promotes cell proliferation via stimulating CCND1 in oesophageal squamous cell carcinoma cells 49 .…”
Section: Mir-17-92 Cluster and Lung Tumorigenesismentioning
confidence: 99%